Finding the relationship between Instructional strategies and Student Learning Styles in Online learning - Our Akemis; Koszalka A. Tiffany (International Journal of Instructional Technology, 2022)
Researchers investigated differences in learner preferences for different types of instructional strategies and learning styles in online environments. Results suggested that matches between students’ learning styles and instructional strategies did not affect their perception of their own learning outcomes, level of effort and involvement, and level of interactions in the course. Data also indicated that no single instructional strategy, among three instructional strategies tested, emerged as superior for high and low field dependent online students.